Effect of different stress conditions with respect to soil and water on rice production - Mohd Khairi Che Lah
Beach Ridges Interspersed with Swales (BRIS) soil is commonly known as problematic soil due to low physical and chemical properties. Low water input rice is the new concern to increase water productivity in agriculture for saving fresh water to be used in municipal purposes. In this study, two experiments were conducted to investigate the effects of compost and different water levels on rice productions. In experiment-I, treatments were laid out in a completely randomized design (CRD) consisting of four different soil treatments were T1: BRISS Soil (control), T2: BRIS soil + Compost (1:1), T3: BRIS soil + Compost (2:1), T4: Topsoil with 5 replications for each treatment. Rice yield, yield parameters. Chlorophyll content, relative water content (RWC) and soil PH were measured. Tiller and panicle numbers, filled grains per panicle, rice yield and straw yields were significantly lower in BRIS soil condition than that of a mixture of compost and BRIS soil condition. On the other hand, plant heights, 1000 seeds weight and unfilled grains per panicle were not significantly different. The treatment (BRIS+compost) significantly increased chlorophyll content but did not affect RWC in leaves. In addition, the pH of soil significantly increased in composting of BRIS soil which indicates an increase of the health of BRIS soil. These results suggest that composting in BRIS soil might improve BRIS soil health and sustain rice yield. In experiment-II, treatment were laid out in a CRD consisting of four different soil water levels were T1: continuous 5cm flooding (control), T2: continuous 1cm flooding, T3: saturated level, T4: alternative wet and dry with 5 replications for each treatment. Different rice cultivars obtained from IRRI were used in this experiment. Plant height, rice yield, yield parameters, chlorophyll content, relative water content (RWC), soil electrical conductivity (EC) and soil pH were measured. Different water level affect rice yield and yield parameters. Plant height was not affected by the different water until before secondary tillering but after that it was decreased under alternative wet and dry condition. Panicle number, tiller number, 1000-seed weight, panicle length were not affected by the different water levels. Filled grains per panicle was significantly lower but unfilled grain per panicle was significantly higher in alternative wet and dry condition in all varieties. Alternative wet and dry water treatment did not affect soil pH but affect chlorophyll content, relative water content in leaves of different rice cultivars. Soil water condition at saturated level or above did not affect rice yield and other plant physiological parameters and soil pH. These results suggest that traditional soil water content of 5cm flooding water is not necessary for rice production. Taken together, it is suggested that poor soil condition might be improved by the application of compost and maintains water condition in soil at 1cm flooding condition so that land coverage in the country for rice production might be increased in ton o fulfill the country demand.